Tindak Tutur Lokusi dalam Film Cinta Laki-Laki Biasa Karya Asma Nadia - Sani Okda Manesa; Irwan Siagian (Departement of Mathematics Education, 2023)
The purpose of this research is to find out the form of locutionary speech acts of locutionary in the film